Ultrasound Evaluation of Congenital Cervical Teratoma and Therapeutic Management (Ex Utero Intrapartum Treatment) - Pablo Padilla Iserte; Amparo Sanroma Pérez; Blanca Ferri Folch; Juan Rubio Moll; Vicente Diago Almela; Alfredo Perales-Marín (Case Reports in Obstetrics and Gynecology)
The ultrasound evaluation of the fetal neck has a high importance as a key point of the airway and digestive tract. We report the case of a fetus diagnosed with a cervical teratoma by ultrasound, which generated a compressive effect on airway, requiring a surgical approach EXIT (ex utero intrapartum treatment) to ensure the extrauterine viability.